2022
DOI: 10.1021/acs.iecr.2c00497
|View full text |Cite
|
Sign up to set email alerts
|

First Measurements for the Simultaneous Sorption of Difluoromethane and Pentafluoroethane Mixtures in Ionic liquids Using the Integral Mass Balance Method

Abstract: Multicomponent absorption measurements are notoriously difficult both experimentally and analytically, which is why the literature is lacking information, even though the results are important for understanding real separation systems. In the case of designing a separation process for hydrofluorocarbon (HFC) refrigerant mixtures using an ionic liquid (IL), it is important to understand multicomponent effects; however, almost all published results are for single component HFC/IL systems. To address this challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…eq is used by the HIsorp software to calculate the moles of species i adsorbed by the adsorbent. The full development of the IMB method was described by Broom et al and has also been discussed by Baca et al…”
Section: Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…eq is used by the HIsorp software to calculate the moles of species i adsorbed by the adsorbent. The full development of the IMB method was described by Broom et al and has also been discussed by Baca et al…”
Section: Models and Methodsmentioning
confidence: 99%
“…eq 46 is used by the HIsorp software to calculate the moles of species i adsorbed by the adsorbent. The full development of the IMB method was described by Broom et al 19 and has also been discussed by Baca et al 45 XEMIS Gravimetric Microbalance. A separate Hiden Isochema XEMIS gravimetric microbalance was used to measure pure gas adsorption isotherms for HFC-125 and HFC-32 with zeolite 5A.…”
mentioning
confidence: 99%
“…Developing a separation process to purify HFCs from refrigerant mixtures can be challenging since many of these mixtures are azeotropic or near azeotropic, making separation difficult to impossible using conventional distillation methods. Only advanced separation processes provide an alternative for recovering refrigerant blends, such as absorption in liquid entrainers, , adsorption on materials such as zeolites, and membrane separation technologies . Project EARTH (Environmentally Applied Research Towards Hydrofluorocarbons) is developing environmentally responsible materials and technology to separate azeotropic HFC mixtures and recycle the pure component refrigerants.…”
Section: Introductionmentioning
confidence: 99%
“…Our extensive analysis of the information available on F-gas absorption in ILs showed that the solubility selectivity for separation of HFC and HFO mixtures could be enhanced using ILs with low molar volume (which is linked to higher charge density in the ions) . Using this knowledge, we previously studied the absorption of HFCs and HFOs in ILs with thiocyanate and dicyanamide anions and obtained the highest selectivity values to date for the separation of R-32 (difluoromethane) and R-134a from R-125 (pentafluoroethane) and R-1234yf, calculated in terms of the ratio of Henry’s law constants at infinite dilution and equilibrium flash separations at 5 bar based on NRTL model calculations. ,, These statements should be validated by means of experimental ternary data as in the recent article by Baca et al , However, the separation of R-134a from R-1234ze­(E) was still found to be difficult because the HFO R-1234ze­(E) is more soluble than its isomer R-1234yf. The rationale behind this difference in solubility is not completely clear because of their very similar physical properties.…”
Section: Introductionmentioning
confidence: 99%